Synthesis and characterization of a Manihot Esculenta-based biodegradable, lignocellulosic reinforced, thermoplastic starch foam material as a plastic foam substitute - Alfante, Iris Angelique V. (2007)
The problems arising from the disposal of large amount of plastic products in decreasingly available landfill facilities may be addressed by waste minimization techniques. Among the waste minimization techniques, source reduction, specifically product changes such as product substitution, is prioritized due to high environmental desirability and substantial impact in minimizing waste. Minimizing plastic waste through platics product substitution would entail developing biodegradable materials that exhibit properties similar to platics. Hence, a biodegradable, lignpcellulosic-reinforced, thermoplastic starch foam material was developed which consists of cassava starch, glycerol, calcium carbonate, agar, carrageanan, water or egg whites and lignocellulosic materials particularly cassava pulp or cassava bark. The mixture is processed through compression/expansion technology utilizing a thermal compressor at a temperature of 220-240C and a pressure of 281.37 psia. The material is subjected to several tests: mechanical strength, water absorption, resistance to chemical reagents and biodegradability using ASTM D 695M-91 & D 638M-91a, ASTM D 570-81(1988), ASTM D 543-87 and ASTM D 5247-92, in order to compare it with existing plastic foam materials. Generally, the results of the tests indicate that the material has comparable properties to that of typical plastic foams, with the exeption of water absorptivity, whic is higher for this new material. For the biodegradability test, fungi and bacteria inoculated samples have lost about 81% of their mass, after 2 weeks. An average of 15% of this mass loss is attributable to the biodegradation of the samples by the fungal and bacterial microorganisms introduced. This demonstrated the material's biodegradability in that aside from the mechanical degradation and degradation from the material's interaction with water, the microorganisms introduced were abe to break down and assimilate the material. 14.3% cassava starch, 42% water and 40% cassava pulp was the composition of the sample having the highest mechanical strength (6111.25 psi compressove strength and 230 psi tensile strength), the highest mass lost due to biodegradation (39.9% ub fungal microorganisms and 7.5% in bacterial microorganisms) and comparable properties upon exposure to chemicals (i.e. sodium hydroxide and toluene). This particular formulation may be used as a substitute forsome plastic foam products in the market, decreasing the amount of non-biodegradable waste that ends up in the landfills.